Fibreoptic‐guided tracheal intubation through i‐gel® and LMA® ProtectorTM supraglottic airway devices ‐ a randomised comparison. (22nd November 2018) - Mendonca, C.; Tourville, C. C.; Jefferson, H.; Nowicka, A.; Patteril, M.; Athanassoglou, V.
Summary: Fibreoptic‐guided tracheal intubation using a supraglottic airway device as a conduit is a technique that can be used in anticipated and unanticipated difficult airway management. Although the i‐gel ® supraglottic airway device has been examined for this purpose, the LMA ® Protector TM, a recently introduced second‐generation supraglottic airway device, has not been evaluated for this use in clinical trials. This prospective, randomised clinical trial compared fibreoptic‐guided tracheal intubation via i‐gel and LMA Protector supraglottic airway devices in two UK hospitals. Patients who were ASA physical status 1 or 2 and undergoing elective surgery requiring tracheal intubation were recruited to the study. A block randomisation list was generated for each study site. The primary outcome measure was time to successful tracheal intubation and secondary outcomes were tracheal intubation success rate, glottic view through flexible fibrescope, ease of tracheal intubation using operator visual analogue score, supraglottic airway device insertion time and insertion success rate. Ninety patients were randomly allocated to each device, and final data analysis was carried out for 92 patients in the i‐gel group and 86 patients in the LMA Protector group. Mean (SD) tracheal intubation time in the i‐gel and LMA Protector groups were 54.3 (13.8) s and 52.0 (13.0) s, respectively (p = 0.240). There were no significant differences in tracheal intubation success rate, glottic view and ease of tracheal intubation between the two groups. This study demonstrates that the LMA Protector supraglottic airway device is comparable to the i‐gel supraglottic airway device as a conduit for fibreoptic‐guided tracheal intubation.